Control and management of a multilevel electric vehicles infrastructure integrated with distributed resources: A comprehensive review - Solanke T.U.; Khatua P.K.; Ramachandaramurthy V.K.; Yong J.Y.; Tan K.M. (Elsevier Ltd, 2023)
Controllers; Decentralized control; Electric power system control; Electric power transmission networks; Electric vehicles; Energy management systems; Level control; Renewable energy resources; Vehicle-to-grid; Control and management; Distributed Energy Resources; Distributed resources; Electricity demands; Internal combustion engine vehicles; Microgrid; Multilevel electric vehicle aggregator; Multilevels; Normal operations; Power grids; Energy management